Recent Updates on Dried Blood Spot and Volumetric Absorptive Microsampling as Microsampling Technique for Antiepileptic Drug Determination: A Systematic Review - Pridilla, Asmiladita; Harahap, Yahdiana; Purwanto, Denni Joko; Maggadani, Baitha Palanggatan (Pharmaceutical Sciences and Research, 2024)
Implementation of Therapeutic Drug Monitoring (TDM) can be useful for patients with uncontrolled seizures. This review article aims to collect and compare the recent development of bioanalytical methods for antiepileptic drugs using microsampling techniques, namely DBS (Dried Blood Spot) and VAMS (Volumetric Absorptive Microsampling). Studies were searched through databases, namely Science Direct, Pubmed, and the Google Scholar search engine using pre-determined keywords. Studies published between 2019 and 2024 and used micro-sampling techniques for antiepileptic drug analysis were included. Non-English studies, non-related studies, duplication, and full text unavailable were excluded. Primary sources were used to build a conclusion regarding the purpose of this review article. A total of 342 articles were identified from databases. From 8 primary studies included, analytical methods for 21 drug compounds as antiepileptic agents and 4 of their metabolites in DBS and VAMS were found. A summary of sample preparation, analytical method, and validation were presented in the narrative form of this review. Concentrations measured using DBS and VAMS demonstrate a strong correlation with conventional matrices; however, conversion factors based on the blood-to-plasma ratio are necessary for accurate comparison. Additionally, the comparison results between DBS and VAMS technique for TDM is still unsatisfactory to prove their interchangeability. Therefore, this comparison needs further evaluation with more samples and more analytes. Analysis of antiepileptic drugs using VAMS is also still limited and further optimization can be carried out to produce more stable, sensitive, fast, and suitable for TDM practice.